A 12-Step Systematic Approach for Curriculum Revision: A Case Study of Undergraduate Nursing Education at Eastern University, Sri Lanka - Youhasan, Punithalingam; Sathaananthan, Thillainathan (Education in Medicine Journal, 2026)
Nursing education must continuously adapt to meet the evolving demands of healthcare. This case study outlines a systematic 12-step approach to revising the undergraduate nursing curriculum at Eastern University, Sri Lanka. The steps include: (a) Identifying needs for curriculum revision; (b) Assessing the educational environment; (c) Revising programme outcomes; (d) Aligning with the national qualification framework; (e) Revisiting the course contents; (f) Organising course content; (g) Choosing educational strategies; (h) Selecting teaching-learning methods; (i) Deciding assessment systems; (j) Way to manage the educational process; (k) Identifying a way to communicate the curriculum; and (l) Meeting the basic requirements of quality assurance. While presented as sequential, the curriculum revision process is inherently dynamic and collaborative, with progress in one step often influencing others. Adopting this systematic approach enables institutions to ensure their programmes remain relevant, responsive to healthcare needs, and capable of producing highly competent nursing graduates.